Validity of five foot and ankle specific electronic patient-reported outcome (ePRO) instruments in patients undergoing elective orthopedic foot or ankle surgery. Issue 1 (January 2021) - Uimonen, Mikko M.; Ponkilainen, Ville T.; Toom, Alar; Miettinen, Mikko; Häkkinen, Arja H.; Sandelin, Henrik; Latvala, Antti O.; Sirola, Timo; Sampo, Mika; Roine, Risto P.; Lindahl, Jan; Ilves, Outi; et al.
Highlights: There are only few valid electronic patient-reported outcomes (ePRO) instruments available for clinicians. The ePRO versions of the FAAM, the FAOS, the MOXFQ, and the VAS-FA provide valid scores for foot and ankle patients. Use of the modified LEFS as an ePRO version for patients with orthopedic foot and/or ankle pathologies is not supported. Abstract: Background: Patient-reported outcomes (PROs) are widely accepted measures for evaluating outcomes of surgical interventions. As patient-reported information is stored in electronic health records, it is essential that there are valid electronic PRO (ePRO) instruments available for clinicians and researchers. The aim of this study was to evaluate the validity of electronic versions of five widely used foot and ankle specific PRO instruments. Methods: Altogether 111 consecutive elective foot/ankle surgery patients were invited face-to-face to participate in this study. Patients completed electronic versions of the Foot and Ankle Ability Measure (FAAM), the Foot and Ankle Outcome Score (FAOS), the modified Lower Extremity Function Scale (LEFS), the Manchester–Oxford Foot Questionnaire (MOXFQ), and the Visual Analogue Scale Foot and Ankle (VAS-FA) on the day of elective foot and/or ankle surgery. Construct validity, coverage, and targeting of the scales were assessed. Results: Based on general and predefined thresholds, construct validity, coverage, and targeting of the ePRO versions of the FAAM, the FAOS, the MOXFQ, and the VAS-FA were acceptable. Major issues arose with score distribution and convergent validity of the modified LEFS instrument. Conclusions: The ePRO versions of the FAAM, the FAOS, the MOXFQ, and the VAS-FA provide valid scores for foot and ankle patients. However, our findings do not support the use of the modified LEFS as an electronic outcome measure for patients with orthopedic foot and/or ankle pathologies.